Instability of Tear Film after Novel Coronavirus Disease: A Noninvasive and No Contact Method by a Scheimpflug-Placido Disc Topographer - Acet, Yakup; Çil, Baris; Kabak, Mehmet; Vural, Esra (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To compare the topographical tear film break-up time (T-BUT) between individuals recovering from COVID-19 and control subjects using a noninvasive and noncontact technique with a Scheimpflug-Placido disc topographer.Methods One-hundred and twenty-two eyes from 61 post-COVID-19 patients and 124 eyes from 62 control subjects were included in this prospective study. All participants underwent detailed ophthalmological examination including best-corrected visual acuity, intraocular pressure measurements, slit lamp examination, and fundoscopy as well as qualitative and quantitative evaluation of the noninvasive first tear film break-up time (NIF-BUT) and noninvasive average tear film break-up time (NIAvg-BUT) with T-BUT measured with a Sirius (CSO – Costruzione Strumenti Oftalmici S. r. l., Italy) corneal topography device.Results The mean NIF-BUT in post-COVID-19 and control patients was 5.2 ± 3.4 vs. 6.5 ± 3.2 sec, respectively. The mean NIAvg-BUT in the corresponding groups was 7.5 ± 3.5 vs. 8.8 ± 3.0 sec, respectively. Both NIF-BUT and NIAvg-BUT were significantly lower in the post-COVID-19 group than in controls (p = 0.004 vs. 0.020). Topographical tear film break-up at any time during the test (17 sec) was observed qualitatively in 79 eyes (64.8%) in the post-COVID-19 group and 57 eyes (46%) in the control group (p = 0.003). Moreover, temporal quadrant involvement occurred significantly more frequently in the post-COVID-19 group (p = 0.028).Conclusion Tear film stability assessment based on T-BUT showed shorter NIF-BUT and NIAvg-BUT in post-COVID-19 patients as compared to the control group. Our results suggest that post-COVID-19 patients have impaired stability of tear film, and therefore require closer monitoring regarding dry eye. In addition, tear film instability in post-COVID-19 patients can be reliably detected using a noninvasive and noncontact technique that is more comfortable for both patients and physicians.
Keywords: novel coronavirus; tear film stability; topographic-BUT; dry eye; noninvasive BUT